EFFECTS OF TOURISM SERVICE QUALITY AND HOTEL QUALITY ON TOURIST SATISFACTION IN DANANG CITY VIETNAM - Trung, Tran Thi (JURNAL NASIONAL PARIWISATA, 2013)
Quality is important to satisfy customers who use its services. In the field of tourism, service quality and quality of the hotel is an important factor to the satisfaction of tourists. In this study, researchers took the subjects of tourism and hotel services in the city of Danang. As for dimensions covering quality of tourism services is the physical evidence (tangible), reliability, responsiveness, empathy, and assurance and the variable quality of the hotel is the location, facilities, services, employees and rates. Several methods of data collection are observation, documentation and interviews with the questionnaire. Analytical methods including validities test, reliability test and multiple regression analysis.Based on these two studies was done in order: First, the perception of tourists with quality services. Second, perceptions of tourists with a quality hotel. Third, find out whether the variable quality of service and variable quality of the hotels have a significant effect on tourist satisfaction Danang city.Results showed lower perceptions of tourists with quality of service assessed by the percentage Very good 28.53% Good 40.33% higher while the rate of 25.07% and the rate Poor Very poor 6.07% lowers. Second, perceptions of tourists with quality hotels rated Very good 31.43%, 41.21% rate good, the Bad and the level of 16.64% 10.71% Very bad. Third, the correlation coefficient R 0.923 indicates a very close relationship between the two independent variables Quality of service and quality hotel with tourist satisfaction. Knot and the quality of hotel service quality significantly influence the satisfaction of tourists in the city of Danang.